2016
DOI: 10.1134/s0869864316020013
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of a numerical simulation method for thermally nonequilibrium dissociating flows in ANSYS Fluent

Abstract: Various issues of numerical simulation of supersonic gas flows with allowance for thermochemical nonequilibrium on the basis of fluid dynamic equations in the two-temperature approximation are discussed. The computational tool for modeling flows with thermochemical nonequilibrium is the commercial software package ANSYS Fluent with an additional userdefined open-code module. A comparative analysis of results obtained by various models of vibration-dissociation coupling in binary gas mixtures of nitrogen and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Here R c vibr , VT is the vibrational energy relaxation rate due to VT transitions for species c . As mentioned previously, the use of the kinetic theory based method for computation of the relaxation times in conjunction with the modified Landau–Teller formula can lead to an improvement in the modeling accuracy for strongly nonequilibrium flows. …”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Here R c vibr , VT is the vibrational energy relaxation rate due to VT transitions for species c . As mentioned previously, the use of the kinetic theory based method for computation of the relaxation times in conjunction with the modified Landau–Teller formula can lead to an improvement in the modeling accuracy for strongly nonequilibrium flows. …”
Section: Theorymentioning
confidence: 99%
“…If one derives the Landau–Teller formula within the Chapman–Enskog framework, a kinetic theory definition of VT relaxation times may be introduced. , It has been shown that VT relaxation times computed using this method are correct in terms of their qualitative behavior at higher temperatures, , and when used with a recently obtained modification of the Landau–Teller formula, can significantly improve the accuracy of numerical modeling of strongly nonequilibrium flows. However, up to now, vibrational relaxation times computed using a kinetic theory definition have been considered only for binary mixtures of nitrogen and oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the inclusion of vibrational kinetics is fundamental for an accurate selfconsistent calculation of the gas temperature, as V-T transfers by collisions with O atoms play a crucial role in gas heating [9]. However, as shown in [59,60], vibrational relaxation in O 2 /O mixtures can be efficiently captured by the modified Landau-Teller formula [43], offering a significant simplification compared to the considerably more complex and costly STS approach. We assume a non-equilibrium Boltzmann distribution of vibrational states at T v , which is a good approximation for the first four vibrational levels at room temperature [61].…”
Section: Vibrational-translational Non-equilibriummentioning
confidence: 99%
“…Details of this technique can be found in [32]. The VT-exchange rate is calculated using the model suggested in [33], which was derived from the kinetic Boltzmann equation with the Chapman-Enskog method.…”
Section: Numerical Methods and Free-stream Conditionsmentioning
confidence: 99%